Определение параметров электрофизической системы для защиты садов от насекомых-вредителей - Адамова, С. В.; Федюшко, Ю. М.; Сасимова, И. А. (НТУ "ХПИ", 2010)
Определены параметры импульсного электрического поля для уничтожения насекомых-вредителей в садах.

Parameters of pulse electric field for destruction of insects-wreckers in gardens are defined.
Definition of parametres in the electrophysical system for protection of gardens against insects-wreckers.
Keywords: садоводство; химические препараты; импульсное электрическое поле; electro physical system; pulse electric field; insects-wreckers